Problemas en el Desarrollo del Lenguaje Oral y su Afectación en el Proceso Aprendizaje de los niños y niñas de 4 a 5 años de edad - Tobar Ronquillo, Silvia Susana (2020)
This research covers a problem identified as: How does oral language affect the Learning Process of children aged 4 to 5 years of the Educational Unit "Victoria Vásconez Cuvi" ?, for which it has proposed as a general objective, Strengthen the Learning process through the development of oral language in children; The research process has worked methodologically based on the Qualitative paradigm; theoretically disaggregating important aspects such as the teaching-learning process, communication, language, the evolutionary characteristics of a child from 4 to 5 years old and the language problems that develop in this age from different perspectives and authors; which has led to systematize the proposal that consists in the establishment of active teaching strategies for the development of oral language in children; It was subsequently concluded that: Based on the situational diagnosis, it has been possible to identify that, in effect, children between 4 and 5 years of age present difficulties in the development of oral language; that it has been feasible to develop a theoretical basis to support each of the contents that contemplate oral language and that; The development and application of the proposal generated have allowed strengthening the Learning process through the development of oral language in children.